PENERAPAN MODEL REALISTIC MATHEMATICS EDUCATION DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN PECAHAN KELAS IV SDN 1 GUNUNGMUJIL TAHUN 2015/2016 - Wulan Sari, Nestiti (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract. The Application of Realistic Mathematics Education Model Using Concrete Media in Improving Mathematics Learning about Fraction for the Fourth Grade Students of SD Negeri 1 Gunungmujil in the Academic Year of 2015/2016. The objectives of this research are to improve Mathematics learning about fraction for the fourth grade students of SD Negeri 1 Gunungmujil. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research showed that the application of RME model using concrete media using appropriate steps can improve Mathematics learning about fraction for the fourth grade students of SD Negeri 1 Gunungmujil in the academic year of 2015/2016. Keywords: RME, concrete media, fraction Abstrak. Penerapan Model Realistic Mathematics Education dengan Media Konkret Dalam Peningkatan Pembelajaran Pecahan Kelas IV SDN 1 Gunungmujil Tahun 2015/2016. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran pecahan siswa kelas IV SDN 1 Gunungmujil. Penelitian ini merupakan PTK kolaboratif. Penelitian dilaksanakan dalam tiga siklus dengan tiap siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Hasil penelitian ini menunjukkan bahwa penerapan model RME dengan media konkret yang dilaksanakan sesuai langkah yang tepat dapat meningkatkan pembelajaran pecahan siswa kelas IV SDN 1 Gunungmujil tahun 2015/2016. Kata kunci: RME, media konkret, pecahan